LOW-COST WORKFLOW FOR 3D URBAN FOREST VIRTUAL RECONSTRUCTION - C. Chioni; A. Murtiyoso; S. Favargiotti; G. A. Massari (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2023)
This contribution addresses, on one hand, the increasing need and demand of 3D data (e.g., point clouds) in urban forestry – for monitoring, analysis, and visualisation purposes –, on the other, the lack of standardised procedures to manage them, also towards engaging and empowering the broader audience. Practitioners in landscape architecture – as a potential bridging field between forestry, geomatics and computer science – could ‘smartly’ manage dynamic ecosystems as forests, parks, and gardens in urban contexts if efficiently provided with digital tools, technologies and techniques for design-oriented information. To this end, a low-cost workflow for 3D virtual reconstruction of under-storey urban vegetation is here proposed to allow exploiting the aesthetic, analytical, and generative potential of 3D point clouds in landscape and urban design. As a proof-of-concept, a combination of a wide range of methods (e.g., spherical photogrammetry, point cloud modelling, virtual reality), tools (e.g., 360° camera, tablet with lidar sensor), and software (e.g., Agisoft Metashape, 3DF Zephyr, CloudCompare, Unity) is tested in the development of a virtual plot of the Mesiano University park in Trento (Italy). Covering all the different steps of the information management activities (namely acquisition, processing, and visualisation), the presented workflow enables a GIS-based, texturized, real-world 3D point cloud rendering of urban forests to be intuitively and interactively experienced in Virtual Reality.